Research into the specifications of woven composites obtained from raffia fibers pretreated using the ecological method. Issue 3 (February 2015) - Kocak, Dilara; Merdan, Nigar; Evren, Oya Burcak
Studies on using cellulosic natural fibers as reinforcement for composites are rapidly growing. The aim of this study is using a raffia-based woven fabric as reinforcement for composites that are grown in the Mediterranean Zone of Turkey. These fabrics benefit from their mechanical performances, low density and their biodegradability. However, it is necessary for the fabrics to form adhesion in the matrix. Therefore, chemical processes should be applied onto the surface of the raffia-based woven fabrics. In this study, three different formulations (different concentrations of maleic anhydride, formic acid and acetic acid) were applied by using conventional and microwave energy on the raffia fabrics. At the end of the application, composite structures were formed by using the fabric as the reinforcement layer and isophtalic polyester as the matrix by the vacuum infusion method. The composite structures were characterized by attenuated total reflectance scanning electron microscope analysis and their mechanical tests were performed through tensile testing. Considering all results, the combination of acetic acid with the microwave process was found to modify the raffia fabric surfaces.